Detecting cardiac contractile activity in the early mouse embryo using multiple modalities - Chen, Chiann-Mun; Miranda, António M. A.; Bub, Gil; Srinivas, Shankar (Frontiers in Physiology, 2015)
The heart is one of the first organs to develop during mammalian embryogenesis. In the mouse, it starts to form shortly after gastrulation, and is derived primarily from embryonic mesoderm. The embryonic heart is unique in having to perform a mechanical contractile function while undergoing complex morphogenetic remodelling. Approaches to imaging the morphogenesis and contractile activity of the developing heart are important in understanding not only how this remodelling is controlled but also the origin of congenital heart defects. Here, we describe approaches for visualising contractile activity in the developing mouse embryo, using brightfield time lapse microscopy and confocal microscopy of calcium transients. We describe an algorithm for enhancing this image data and quantifying contractile activity from it. Finally we describe how atomic force microscopy can be used to record contractile activity prior to it being microscopically visible.